Social–Ecological Factors Influencing Mosquito Presence in Livestock Areas: Implications for Vector Control - Santjaka, Aris; ., Sunaryo; Utomo, Nur; Firdaust, Mela; Ma’ruf, Fauzan; Wardhono, Hari Rudijanto Indro; Amaliyah, Nurul; Lukmitarani, Ratih; Yusmiati, Siti Nur Husnul; Mastuti, Dewi Nugraheni Restu; et al. (Journal of Cultural Analysis and Social Change, 2026)
Malaria elimination strategies have predominantly targeted the domestic sphere, yet persistent transmission in endemic clusters indicates that malaria is embedded within broader socio-ecological relations linking humans, livestock, and the environment. This study analyzes the socio-ecological dynamics of malaria transmission in an endemic area of Purworejo District, Indonesia, integrating entomological, spatial, and qualitative approaches. A mixed-methods design combined spatial mapping, a quasi-experimental time-series intervention through the installation of long-lasting insecticidal nets (LLINs) in livestock shelters, repeated mosquito collections, and in-depth interviews with livestock owners. The intervention reduced Anopheles spp. density by 75.44% overall and 98.71% indoors. Mixed linear model analysis confirmed that time, species, location, and their interactions significantly shaped mosquito abundance (p < 0.001), indicating that vector control outcomes are contextually embedded. Post-intervention stability suggests the formation of a new ecological equilibrium at a lower density. Qualitative findings show that reduced mosquito nuisance and improved livestock comfort reshaped community perceptions and strengthened willingness to participate in malaria control. The study reframes livestock shelters as critical yet overlooked transmission nodes and positions malaria control as a socio-ecological transformation rather than a purely technical intervention.